2015
DOI: 10.1093/jxb/erv419
|View full text |Cite
|
Sign up to set email alerts
|

A small indel mutation in an anthocyanin transporter causes variegated colouration of peach flowers

Abstract: HighlightAn anthocyanin transporter gene that contains a high frequency of non-transposable element-related mutations is responsible for variegated colouration of flowers in peach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 72 publications
4
62
0
Order By: Relevance
“…The involvement of GSTs in trafficking and accumulation of anthocyanins have been verified in maize (Marrs et al, 1995), petunia (Mueller et al, 2000), Arabidopsis (Sun et al, 2012), cyclamen (Kitamura et al, 2012), perilla , grape (Conn et al, 2008), apple (Jiang et al, 2019) and litchi (Hu et al, 2016). In this study, we found a GST (PpGST1), with GeneID (Prupe.3G013600, also previously as ppa011307m) later found to be identical to that of an anthocyanin transporter (Riant) related to the variegated coloration of peach flowers (Cheng et al, 2015), was differentially expressed in 'HJ' and 'YL' throughout developmental stages, which may account for the distinct anthocyanin accumulation in the fruit of two cultivars. Also, the transcription of PpGST1 was consistent with anthocyanin contents of peel and flesh in different cultivars.…”
Section: Discussionsupporting
confidence: 69%
“…The involvement of GSTs in trafficking and accumulation of anthocyanins have been verified in maize (Marrs et al, 1995), petunia (Mueller et al, 2000), Arabidopsis (Sun et al, 2012), cyclamen (Kitamura et al, 2012), perilla , grape (Conn et al, 2008), apple (Jiang et al, 2019) and litchi (Hu et al, 2016). In this study, we found a GST (PpGST1), with GeneID (Prupe.3G013600, also previously as ppa011307m) later found to be identical to that of an anthocyanin transporter (Riant) related to the variegated coloration of peach flowers (Cheng et al, 2015), was differentially expressed in 'HJ' and 'YL' throughout developmental stages, which may account for the distinct anthocyanin accumulation in the fruit of two cultivars. Also, the transcription of PpGST1 was consistent with anthocyanin contents of peel and flesh in different cultivars.…”
Section: Discussionsupporting
confidence: 69%
“…This suggests that PpUFGT encodes a rate-limiting enzyme that determines the overall rate of anthocyanin biosynthesis, which supports the previous finding of PpMYB10.1 activating UFGT in tobacco 57 . Besides PpUFGT, an anthocyanin transporter gene PpGST was also significantly activated, which is consistent with previous reports that GST acts downstream of anthocyanin-related MYB gene MYB10.1 59,60 . These results demonstrate that our newly developed transgenic root system has applications in functional characterization of genes and genetic engineering in peach or its related fruit trees of the Rosaceae family.…”
Section: Discussionsupporting
confidence: 92%
“…A TT2-like R2R3-MYB gene, designated Peace , regulates petal pigmentation in flowering peach ‘Genpei’ bearing variegated and fully pigmented flowers although it is unclear whether the Peace gene is able to activate anthocyanin and/or proanthocyanin pathway structural genes ( Uematsu et al, 2014 ). However, our study shows that a small indel mutation in an anthocyanin transporter, which is not the result of a transposon insertion or excision, causes variegated colouration of flowers of ornamental peach, ‘Hongbaihuatao’ ( Cheng et al, 2015 ). These results suggest a complex mechanism regulating anthocyanin accumulation in peach flower.…”
Section: Introductionmentioning
confidence: 71%